THE MOTIVE OF A JOURNEY AND THE COMPOSITION OF A FAIRY TALE - Mashrapova Gulsanam Axadovna (Journals Park Publishing, 2024)
Numerous reflections have been made in folklore studies regarding the relationship between motive and plot. These two elements, which are interdependent, are among the topics that scholars in the field have paid the most attention to. In our opinion, the epic plot is formed by a 'chain reaction' of semantically related motives. Each of these motives, within this chain, holds its own place and function”.
Keywords: fairy tale, motive, composition, exposition, medial, final.